Impact of Stubble Incorporation on Soil Properties, Growth and Yield of Wheat in Semi-Arid Conditions (Journal of Agriculture and Biology, 2025)
Soil organic carbon (SOC) typically decline under intensive cropping system. Decrease in SOC might be linked with conventional tillage and poor stubble management. In arable soils, substantial losses of SOC occur due to cultivation, insufficient incorporation of nitrogen rich stubbles, extended fallow periods, and excessive nitrogen fertilizer use. This experiment was conducted at MNS-University of Agriculture, Multan’s research farm (C-block), to evaluate the effects of stubble incorporation on soil health and wheat productivity. Stubbles were incorporated in soil approximately two - three week before sowing. The experiment followed a Randomized Complete Block Design using split plot arrangements, comprising six treatments and three replications. Three levels of irrigation were applied 100 %, 75 %, and 50 %, respectively. Soil moisture contents was measured weekly using the gravimetric method. Plant height were also recorded weekly. At harvest, data on yield and yield contributing parameters were collected. Soil samples were taken at the beginning and end of the experiment for nutrient analysis. Our results revealed that average maximum yield of wheat crop under stubble incorporation was 6.69 Mg ha-1, compared to 5.4 Mg ha-1 in control (no stubble incorporation) treatments. Soil organic carbon under stubble incorporation reached 9.06 g kg-1 of soil sample as compared to control treatment organic carbon was obtained 5.86 g kg-1 of soil whereas the control recorded 5.86 g kg-1. .